Gaussian filter based à-trous algorithm for image fusion - Vekkot, Susmitha; Shukla, Pancham (ACM, 2015)
Image fusion integrates complementary information from various perspectives in order to provide a meaningful interpretation of useful features and textures in multisource images. Here, we present a multiresolution algorithm based on Stationary Wavelet Transform for fusion of two test images of same size. The algorithm uses a Gaussian low-pass filtering technique for the high frequency subbands of SWT decomposition. The new approach gave sharper edges and structural enhancement than region based approaches involving calculation of energy around salient features. The key feature of Gaussian filtering is the flexibility of using filters with different values for standard deviation depending on the application and the range of detail necessary for processing.